2013
DOI: 10.1097/sih.0b013e318273101a
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Can Contribute a Part of Cardiorespiratory Physiotherapy Clinical Education

Abstract: An SLE can replace clinical time in cardiorespiratory physiotherapy practice. Part education in the SLE satisfied clinical competency requirements, and all stakeholders were satisfied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
197
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(206 citation statements)
references
References 26 publications
7
197
0
2
Order By: Relevance
“…The students' and CEs' rating of SLE Model 1 may indicate that SLE Model 2 (first 2 weeks 50% SLE, 50% clinical internship, followed by 2 weeks of full clinical internship) was slightly more beneficial, as the students spent at least some time in the clinical environment throughout the 4 weeks. 29 The strong, multi-site experimental design and large sample sizes make these studies very robust, and their findings support the hypothesis that SLE can yield similar learning outcomes and replace clinical time, with a slight preference for SLE Model 2. This is incredibly encouraging for faculty responsible for the clinical education components of PT curricula, who are sometimes challenged to find an adequate variety and number of clinical learning experiences.…”
Section: Group D: Using Simulation To Represent Clinical Education (7supporting
confidence: 50%
See 4 more Smart Citations
“…The students' and CEs' rating of SLE Model 1 may indicate that SLE Model 2 (first 2 weeks 50% SLE, 50% clinical internship, followed by 2 weeks of full clinical internship) was slightly more beneficial, as the students spent at least some time in the clinical environment throughout the 4 weeks. 29 The strong, multi-site experimental design and large sample sizes make these studies very robust, and their findings support the hypothesis that SLE can yield similar learning outcomes and replace clinical time, with a slight preference for SLE Model 2. This is incredibly encouraging for faculty responsible for the clinical education components of PT curricula, who are sometimes challenged to find an adequate variety and number of clinical learning experiences.…”
Section: Group D: Using Simulation To Represent Clinical Education (7supporting
confidence: 50%
“…The second study used a similar design, but the cases focused on musculoskeletal diagnoses using SPs. 30 Neither study 29,30 found any differences in the main outcome, the Assessment of Physiotherapy Performance (APP), between traditional clinical immersion and either SLE model, which suggests that structured SLE is a viable substitute for hard-to-find clinical experiences. Secondary outcomes for both studies included students' self-rated confidence in communicating with, assessing, and managing patients.…”
Section: Group D: Using Simulation To Represent Clinical Education (7mentioning
confidence: 99%
See 3 more Smart Citations